Communication in Health Care Services: An Overview of the Legal Position of Informed Consent - Muhammad Hatta; Cut Khairunnisa; Sri Wahyuni (International Journal of Law, Social Science, and Humanities, 2024)
The principle of informed consent requires physicians to communicate with patients before administering medical treatment. The information provided by physicians serves as a guide or consideration for patients when making an informed decision and gives the physician permission to proceed with the medical intervention. The obligation of physicians to communicate effectively has been regulated in Articles 35 and 45 of Law No. 29 of 2004 concerning Medical Practice and further strengthened by the Regulation of the Minister of Health of the Republic of Indonesia No. 290/ Menkes/ Per/ III/ 2008 concerning Approval of Medical Measures. Effective communicationin health care services cannot be exaggerated when it comes to providing medical care. Before the administration of medical treatment, the patient had already been informed of his condition, the probability of recovery, the potential risks associated with treatment and alternative therapy methods to ensure that patients were well informed about the disease and procedures that would be performed by physicians. Efficient communication between patients and healthcare providers is crucial to preventing medical malpractice.